Bespoke Language Teaching (BLT): A proposal for a theoretical framework. The case of EFL/ELF for Italians - Santipolo, Matteo (Studies in Second Language Learning and Teaching, 2017)
This paper deals with the problems of teaching English as a foreign language (EFL) and as a lingua franca (ELF) in the Italian educational system and, in particular, with introducing language variation in the English class. After briefly illustrating how English teaching has changed in the last few decades, an outline is drawn of what happens in the Italian school system today from child care to university as far as English teaching is concerned. The second part of the contribution focuses on the increasing variability of English as a world language, both within and outside the native speakers’ domain. The second part also deals with the issues that the complex nature of variation in English has raised when teaching it, and underlines how such issues have recently, although only partially, been acknowledged by the Italian Ministry of Education. The final section, illustrates a proposal for implementing the teaching of English variation in Italian schools, based on the concepts of utility and usability which have given birth to a student-tailored approach called Bespoke Language Teaching.